Moko Symbolization As Socio-Religious Harmony of Alor Society in East Nusa Tenggara - Iswanto, Iswanto; Kawanggung, Yudhi (Balai Penelitian dan Pengembangan Agama Semarang, 2021)
The understanding of moko is related to the identity of the Alor people. Historically, moko was brought from Vietnam and became a heirloom which was passed down from generation to generation. In practice, moko can be used as a dowry of marriage, clan identity, musical instruments, and several other uses. This study provides novelty on the moko symbolization as a socio-religious harmony of Alor society. The problem to be resolved in this research is “how does the moko symbolize socio-religious harmony in the people of Alor, East Nusa Tenggara?” The theoretical concept used in this article is Geertz’s ‘religious as the cultural system” which is paired with Epicurus' opinion about the three levels of harmony. This study used the phenomenological method of Edmund Husserl. The results of this study are moko symbolization as a rhythmic leader of musical instruments related with social messages in the ownership it and the function of moko as a dowry of marriage. In addition, the results of the study also show that the symbolization of moko becomes a part of the harmony embodiment in the life of the Alor people. This symbolization process occurs at the level of ideas and manifests in behavior. The novelty in this research is the characteristics of the Alor community as a heterogeneous society place the symbols of a set of conventions. Moko as part of the convention symbol embodies social harmonization. This part becomes an interesting character because moko is not an original object from the Alor community, but it has been adopted as a cultural symbol. Social harmonization occurs at the level of ideas which are adhered to customary law. This really depends on the values held in society.